1995
DOI: 10.1073/pnas.92.26.11975
|View full text |Cite
|
Sign up to set email alerts
|

Differential replication of a single, UV-induced lesion in the leading or lagging strand by a human cell extract: fork uncoupling or gap formation.

Abstract: We have constructed simian virus 40 minireplicons containing uniquely placed cis,syn-thymine dimers (T< >T) for the analysis of leading-and lagging-strand bypass replication. Assaying for replication in a human cellfree extract through the analysis of full-size labeled product molecules and restriction fragments spanning the T< >T site resulted in the following findings: (i) Despite these investigations, a basic understanding of replication of damaged DNA in normal human cells is lacking (2).In vitro studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 24 publications
7
84
0
Order By: Relevance
“…However, human pol δ cannot replicate past them, suggesting that disassembly of the pol δ holoenzyme on encountering such lesions is predominantly driven by an abrupt decrease in k pol . Indeed, blockage of strand elongation by human pol δ was observed directly 3′ to these lesions rather than upstream (8,44,45,50). The results presented in Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, human pol δ cannot replicate past them, suggesting that disassembly of the pol δ holoenzyme on encountering such lesions is predominantly driven by an abrupt decrease in k pol . Indeed, blockage of strand elongation by human pol δ was observed directly 3′ to these lesions rather than upstream (8,44,45,50). The results presented in Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In similar fashion, on SV40-based plasmids containing a single unique site CPD in the lagging strand template, synthesis of the Okazaki fragment containing the CPD lesion was selectively inhibited compared with the flanking fragments. Furthermore, strand elongation past and beyond the lesion was observed in only a fraction of the analyzed molecules (50,61). Altogether, these observations suggest that the lagging strand template is reprimed 5′ to the damage, and pol δ is recycled to nascent primers upstream of the damage, leaving behind a ssDNA gap extending from the CPD lesion to the 5′ terminus of the downstream Okazaki fragment.…”
Section: Discussionmentioning
confidence: 72%
“…Studies in mammalian cells of replicating UV-irradiated plasmids have revealed DNA polymerase stalling on both the leading and lagging strands and showed the existence of ssDNA gaps on the lagging strand, presumably caused by interruption of Okazaki fragment synthesis [41][42][43][44]. This suggests that DSGs also arise during mammalian DNA replication, although it is not yet clear whether they can form on the leading strand.…”
Section: Relationship Between Dna Polymerase Stalling and Hrmentioning
confidence: 99%
“…In particular, a polymeraseblocking lesion on the lagging strand template should not arrest replication, as it proceeds with synthesis of the next Okazaki fragment. The result is a lagging strand with a gap comprising the lesion (Svoboda and Vos, 1995) to be repaired at a later time, after gap filling, by either TLS or HR. Although a similar mechanism has been proposed, when the leading strand polymerase stops at a lesion on the template (Heller and Marians, 2006;Lopes et al, 2006), an alternative possibility is decoupling of the leading and lagging strand polymerase with the lagging strand being further elongated for another 1 or 2 kb (Cordeiro-Stone et al, 1999;Pagés and Fuchs, 2003).…”
Section: Introductionmentioning
confidence: 99%